On site visual detection of Porphyromonas gingivalis related periodontitis by using a magnetic-nanobead based assay for gingipains protease biomarkers - Alhogail, Sahar; Suaifan, Ghadeer A. R. Y.; Bizzarro, Sergio; Kaman, Wendy E.; Bikker, Floris J.; Weber, Karina; Cialla-May, Dana; Popp, Jürgen; Zourob, Mohammed (Microchimica Acta, 2018)
Porphyromonas gingivalis (P. gingivalis) is a pathogen causing periodontitis. A rapid assay is described for the diagnosis of periodontal infections related to P. gingivalis. The method is making use of gingipains, a group of P. gingivalis specific proteases as a detection biomarker. Magnetic-nanobeads were labeled with gingipain-specific peptide substrates and immobilized on a gold biosensing platform via gold-thiol linkage. As a result of this, the color of the gold layer turns black. Upon cleavage of the immobilized substrates by gingipains, the magnetic-nanobeads-peptide fragments were attracted by a magnet so that the golden surface color becomes visible again. This assay is highly sensitive and specific. It is capable of detecting as little as 49 CFU·mL−1 of P. gingivalis within 30 s. Examination of periodontitis patients and healthy control saliva samples showed the potential of the assay. The simplicity and rapidity of the assay makes it an effective point-of-care device. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-20
Keywords: Biosensor; Colorimetric assay; Diagnosis; Gingivitis; Magnetic nanoparticles; Periodontal diseases; Point of care; Porphyromonas gingivalis